PENGARUH PROFITABILITAS, LEVERAGE, PERTUMBUHAN PENJUALAN, DAN DEWAN KOMISARIS TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2021 - Tagor Sidauruk; Adolpino Nainggolan; Restu Juliandhary (Jurnal Liabilitas, 2023)
This research was conducted to understand the impact of Profitability, Leverage, Sales Growth and the Board of Commissioners regarding Tax Avoidance. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange for the 2019 – 2021 term. Sampling used a purposive sampling method, totaling 88 samples. The research results were obtained by using multiple linear regression analysis method. The results of this research argue that the Leverage variable has a significant influence on tax evoidance and is not influenced by the Profitability, Sales Growth, and Board of Commissioners variables.